Prevalence of chronic kidney disease in Western Australia, 2010–2020 - Delia Hendrie; Crystal Man Ying Lee; Suzanne Robinson; Aron Chakera; James Boyd; Elizabeth Thomas; Sean Randall; Madison Frith; Kevin Chai; Kanika Mehta; Mohamed Estai (BMJ Open)
Objective To assess the prevalence and trends of chronic kidney disease (CKD) in Western Australia (WA) from 2010 to 2020 using linked pathology data.Design A retrospective observational cohort study using linked de-identified data from WA pathology providers, hospital morbidity records and mortality records.Setting A Western Australian population-based study.Participants All individuals aged 18 years and older with at least one serum creatinine test.Primary outcome measure CKD status as determined by estimated glomerular filtration rate and urine albumin-creatinine ratio.Results Analysing data from 2 501 188 individuals, there was a significant increase in age-sex standardised CKD prevalence from 4.7% in 2010 to 6.0% in 2020, with annual average percentage change of 3.0% (95% CI: 2.3% to 3.7%). Prevalence of CKD stages 3 and above was 4.8% in 2020. Higher CKD prevalence was observed in regional and remote areas compared with major cities, and among individuals in the most socioeconomically disadvantaged quintiles. Sensitivity analysis indicated minor impacts from data exclusions and methodological choices.Conclusions CKD prevalence in WA has been steadily increasing, reflecting broader Australian trends. The study highlights significant disparities in CKD prevalence based on age, socioeconomic status and geographic remoteness.